2012
DOI: 10.1227/neu.0b013e31823c40fe
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator-Based Stereotactic Radiosurgery for Brainstem Metastases

Abstract: Linac-SRS using a median dose of 14 Gy provided excellent local control in patients with brainstem metastases less than 0.4 mL with relatively low serious morbidity. The results of the study support the use of linac-SRS for patients with brainstem metastases. We advocate 14 to 16 Gy, given the high local control rate and low complication rate with this dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…(Table 4) and our overall survival was comparable to other studies. Relative to other studies that reported WBRT doses up to 45 Gy combined with SRS to the brainstem, the WBRT doses employed in our study were lower and hypofractionated [11, 12, 1719, 22, 23], but outcomes were similar to published series. The impact of WBRT dose on local control and toxicity when used in conjunction with brainstem SRS has not been investigated or reported previously.…”
Section: Discussionsupporting
confidence: 65%
“…(Table 4) and our overall survival was comparable to other studies. Relative to other studies that reported WBRT doses up to 45 Gy combined with SRS to the brainstem, the WBRT doses employed in our study were lower and hypofractionated [11, 12, 1719, 22, 23], but outcomes were similar to published series. The impact of WBRT dose on local control and toxicity when used in conjunction with brainstem SRS has not been investigated or reported previously.…”
Section: Discussionsupporting
confidence: 65%
“…As a result, a dose threshold, volume threshold, or other prognostic factor that can estimate radiation-related toxicity was not developed. Although the existing studies demonstrated statistically significant results and recommendations regarding brainstem SRS, other reports have failed to demonstrate a dose-response relationship (11-18, 27-30). …”
Section: Discussionmentioning
confidence: 91%
“…The literature notes conflicting recommendations regarding the optimum margin dose to maximize the therapeutic ratio (17, 18, 20, 21). Although some small series demonstrated improve local control with the use of doses of at least 15 to 20 Gy (20-22), other series recommend tumor margin doses as low as 12 Gy(18, 26). Additionally, the radiosurgical technology used may affect the rate of fall-off of radiation beyond the tumor margin and impact toxicity rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations